The Effectiveness of Modified Dictogloss in Promoting Receptive and Productive Knowledge of Collocation - Rohmah, Mufidatur (Universitas Negeri Surabaya, 2023)
This study focused on exploring how the dictogloss task of text reconstruction could enhance the learning of English collocation, especially phrasal verbs. Earlier studies have shown that learners face challenges when it comes to utilizing these word combinations, yet there are limited effective instructional techniques available. The participants in this research were 84 Islamic senior high school students in the eleventh grade (aged 16-17). The study employed a true experimental design to compare the effectiveness of two modified versions of the dictogloss task. In this study, the participants were randomly allocated to three groups: experimental group 1 (SEM), experimental group 2 (STRUC), and a control group (traditional).The students worked in pairs and reconstructed English texts containing the target items (phrasal verbs). Before each reconstruction, a priming activity was conducted with the intention of assisting learners in perceiving collocation (phrasal verbs). The result demonstrated that students who performed modified dictogloss gained higher mean scores in post-tests of receptive and productive knowledge of collocation compared to students who performed traditional dictogloss. Furthermore, engaging students in a pre-task activity that involved elaborating on the meaning of collocations outperformed a form-focused pre-task activity, particularly in terms of productive knowledge. The results are extensively analyzed in connection with previous research, highlighting their implications for English language teaching (ELT) and future research.